Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/srep42725
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-6 regulates pro-fibrotic TGF-β responses in neonatal mouse ventricular cardiac fibroblasts

Abstract: Fibulin-6, an essential component of extracellular matrix determines the architecture of cellular junctions in tissues undergoing strain. Increased expression and deposition of fibulin-6 facilitates fibroblast migration in response to TGF-β, following myocardial infarction in mouse heart. The underlying mechanism still remains elusive. In conjunction with our previous study, we have now demonstrated that in fibulin-6 knockdown (KD) fibroblasts, not only TGF-β dependent migration, but also stress fiber formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…That HMCN1 proteins assemble into tracks suggests a role for HMCN1 in structural support. Data from a mouse model of myocardial infarction and from cultured cardiac fibroblasts suggest that HMCN1 functions in myocardial remodeling by regulating profibrotic TGB‐β responses . It is possible that HMCN1 also plays important roles in remodeling of the tissues examined in our study during development and in response to injury.…”
Section: Discussionmentioning
confidence: 81%
“…That HMCN1 proteins assemble into tracks suggests a role for HMCN1 in structural support. Data from a mouse model of myocardial infarction and from cultured cardiac fibroblasts suggest that HMCN1 functions in myocardial remodeling by regulating profibrotic TGB‐β responses . It is possible that HMCN1 also plays important roles in remodeling of the tissues examined in our study during development and in response to injury.…”
Section: Discussionmentioning
confidence: 81%
“…Insulin and contraction are the two key stimuli that acutely regulate Glut4 recruitment to the plasma membrane of the heart, and cardiac fibroblast contractility is one of the characteristics of myocardial remodeling [ 44 ]. These two stimuli initiate distinct signaling mechanisms, but both lead to increased Glut 4 translocation and glucose uptake [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-6 is upregulated in the ischemic myocardium, especially in the infarct border zone, but, paradoxically, TGF-β treatment in isolated mouse cardiac fibroblasts inhibits fibulin-6 expression, indicating complex involvement of fibulin-6 in TGF-β signaling [ 147 ]. Further investigation by the same group demonstrated that fibulin-6 plays an important role in regulating TGF-β-mediated responses by enhancing TGF-β receptor dimerization and activation to further trigger downstream pathways [ 148 ]. The interaction between other newer fibulins, fibulin-7 and -8, and TGF-β has not been identified.…”
Section: Interaction Between Fibulins and Tgf-βmentioning
confidence: 99%
“…Fibulin-5 expression is enhanced by TGF-β [ 121 , 122 , 142 , 146 ], and fibulin-5 promotes TGF-β-induced EMT through activating MMP-2 and -9 in mammary epithelial cells [ 122 ], suggesting bidirectional interaction similar to fibulin-2. Fibulin-6 plays a role in negative feedback loop in regulating TGF-β-mediated profibrotic response in neonatal mouse ventricular cardiac fibroblasts [ 148 ], similar to fibulin-1. Each fibulin appears to have a unique biological profile in relation to TGF-β signaling in a context-dependent manner.…”
Section: Biological Significance Of Fibulins and Tgf-β Signalingmentioning
confidence: 99%